KLHL5 Is a Prognostic-Related Biomarker and Correlated With Immune Infiltrates in Gastric Cancer - Wu, Qiulin; Yin, Guobing; Lei, Jinwei; Tian, Jiao; Lan, Ailin; Liu, Shengchun (Frontiers in Molecular Biosciences, 2020)
Background: KLHL5 (Kelch Like Family Member 5) is differentially expressed in gastric cancer, but its correlation with prognosis and the mechanism of function in gastric cancer remain unclear. Methods: KLHL5 expression in a variety of cancers was evaluated using the Oncomine database and TIMER. The correlation between KLHL5 expression and patient prognosis was determined using the Kaplan-Meier plotter, Gene Expression Profiling Interactive Analysis (GEPIA), and PrognoScan databases. Further, the relationship between the expression of KLHL5 and profiles of inflammatory infiltrates was determined using TIMER. Finally, the correlative significance between KLHL5 expression and immune marker sets was explored using GEPIA and TIMER. Results: KLHL5 was found to be differentially expressed and correlated with clinical outcomes in several types of cancers in The Cancer Genome Atlas database. Specifically, KLHL5 mRNA expression was upregulated and correlated with poorer overall survival and progression-free survival in gastric cancer. Moreover, elevated KLHL5 expression was significantly correlated with lymph node stage, infiltration level, and expression of multiple immune marker sets. Conclusions: These results suggest that KLHL5 expression is closely linked to clinical outcomes and microenvironmental infiltration levels in different neoplasms. This study also indicates that KLHL5 is a modulator of inflammatory cell recruitment, shaping the landscape of immune cell infiltration. Thus, KLHL5 is a potential prognostic predictor for gastric malignancy.